2023
DOI: 10.3389/fonc.2023.1223857
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of nomogram models to predict radiotherapy or chemotherapy benefit in stage III/IV gastric adenocarcinoma with surgery

Xiangqing Ren,
Tian Huang,
Xiaolong Tang
et al.

Abstract: ObjectivesThe advanced gastric adenocarcinoma (GAC) patients (stage III/IV) with surgery may have inconsistent prognoses due to different demographic and clinicopathological factors. In this retrospective study, we developed clinical prediction models for estimating the overall survival (OS) and cancer-specific survival (CSS) in advanced GAC patients with surgeryMethodsA retrospective analysis was conducted using the Surveillance, Epidemiology, and End Results (SEER) database. The total population from 2004 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…At the same time, the adverse reaction rate of the combined group was lower. Compared with the INT-0116 study and the ARTIST study, this study revealed a lower incidence of grade 3–4 gastrointestinal adverse reactions, which may be partly related to the application of IMRT[ 25 ]. Studies have confirmed that IMRT is superior to 2D or 3D radiotherapy because it provides a more accurate dose distribution for the planned target area and reduces the risk of radiation-related adverse reactions[ 26 - 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the adverse reaction rate of the combined group was lower. Compared with the INT-0116 study and the ARTIST study, this study revealed a lower incidence of grade 3–4 gastrointestinal adverse reactions, which may be partly related to the application of IMRT[ 25 ]. Studies have confirmed that IMRT is superior to 2D or 3D radiotherapy because it provides a more accurate dose distribution for the planned target area and reduces the risk of radiation-related adverse reactions[ 26 - 28 ].…”
Section: Discussionmentioning
confidence: 99%